2012
DOI: 10.1097/mpa.0b013e31824ac3a5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Serum of Human K-ras Oncogene Transgenic Rats With Pancreatic Ductal Adenocarcinomas

Abstract: We identified 4 previously unreported miRNAs (miRNA-203, miRNA-369-5p, miRNA-376a, and miRNA-375) whose expression is significantly different in PDAC rats compared to control rats. These miRNAs need to be quantitated in humans as potential novel clinical diagnostic biomarkers for PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…These findings suggest that these differentially expressed miRNAs in pancreatic cancer could serve as circulating biomarkers in the blood and body fluids of patients with this disease. Several studies found that circulating miR-155 was upregulated in the serum or plasma (Wang et al, 2009;Kong et al, 2011;Liu et al, 2012;Yabushita et al, 2012) of patients with pancreatic cancer and in pancreatic juice or cystic fluid samples (Sadakari et al, 2010;Wang et al, 2015). One study found that miR-10 and miR-100 were also upregulated in the plasma of patients with pancreatic cancer (LaConti et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…These findings suggest that these differentially expressed miRNAs in pancreatic cancer could serve as circulating biomarkers in the blood and body fluids of patients with this disease. Several studies found that circulating miR-155 was upregulated in the serum or plasma (Wang et al, 2009;Kong et al, 2011;Liu et al, 2012;Yabushita et al, 2012) of patients with pancreatic cancer and in pancreatic juice or cystic fluid samples (Sadakari et al, 2010;Wang et al, 2015). One study found that miR-10 and miR-100 were also upregulated in the plasma of patients with pancreatic cancer (LaConti et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, down regulation of let-7 was observed in the FNA from PC patients [60]. In addition, many other studies have reported significantly higher serum concentration of miR-210, miR-18a, and miR-155 in PC patients compared to healthy controls [50, 215, 216] and concentration of blood circulating miR-155, miR-21 and miR-210 was significantly higher in rats with PC [228]. Although, differentially expressed miR-27a-3p in PBMCs can sufficiently discriminate PC from benign pancreatic/peri-pancreatic diseases (BPD) with a sensitivity of 82.2% and specificity of 76.7% (AUC= 0.840), combination of miR-27a-3p expression in PBMC and CA19.9 serum levels had significantly higher diagnostic accuracy than either of them alone with a sensitivity of 85.3% and specificity of 81.6% (AUC= 0.886) [221].…”
Section: Potential Role Of Mirnas In Pancreatic Cancer Diagnosismentioning
confidence: 86%
“…Over expression of the above mentioned four miRNAs in pancreatic juice was further associated with reduced overall survival (OS) and lymph node metastasis [229]. Not only in humans, PC bearing rats also showed increased blood levels of miR-155, miR-21 and miR-210 compared to normal control [228]. Similarly, high levels of circulating miR-196a and -196b was observed in KPC (Kras G12D ;Trp53 R172H ;Pdx1-Cre) mice with PanIN2/3 lesions as well as PDAC as compared to contemporary littermate control or KPC mice with PanIN1 lesions.…”
Section: Potential Role Of Mirnas In Pancreatic Cancer Diagnosismentioning
confidence: 99%
“…The expression of miR-106b-5p was up-regulated in glioma tumor tissues, and played critical roles in glioma tumorigenesis . Meanwhile, miR-30b-5p was reported to be up-regulated in regulatory T cells (Tregs) from HCC patients , and it was also increased in the serum from rats bearing pancreatic ductal adenocarcinoma (Yabushita et al, 2012). In addition, the overexpression of miR-30b-5p was also reported to inhibit gastric cancer cell migration (Qiao et al, 2014).…”
Section: Cells In Vitromentioning
confidence: 97%